Research on solid waste management system to improve existing situation in Corlu Town of Turkey - Tinmaz, Esra (Waste management (New York, N.Y.), 2006)
Over the past decades, uncontrolled population growth and rapid urbanization and industrialization have resulted in environmental problems in Corlu Town, Turkey. One of the most important problems is solid waste due to inadequate management practices. Nowadays, increasing public awareness of the environment compels local authorities to define and to adopt new solutions for waste management. This paper presents a general overview of current solid waste management practices in Corlu Town and principles of the recommended municipal solid waste (MSW) management system. In Corlu, 170 tonnes of municipal solid waste are generated each day, or 1.150 kg per capita per day. Approximately one-half of the municipal solid waste generated is organic material and 30% of the MSW consists of recyclable materials. The recommended system deals with maximizing recycling and minimizing landfilling of municipal solid waste, and consists of separation at source, collection, sorting, recycling, composting and sanitary landfilling. This study also analyzed the recommended system with respect to feasibility and economics. To evaluate whether the suggested system is cost effective or not, the operating cost of the recommended system and market prices of recyclable materials were compared, and the results show that the recommended system will reduce required landfill volume up to 27% of compared to the present situation. The profit of the recommended system is estimated to be about 80 million US dollars